Intussusception Related to Small Intestinal Lipomas: A Case Report and Review of the Literature - Hu, Qiang; Wu, Jinfeng; Sun, Yuanshui (Frontiers in Surgery, 2022)
Introduction: Adult intussusception is a rare disease that is difficult to diagnose and treat, and is even rarer when it is caused by lipoma of small intestine. We reported a case of small intestine lipoma combined with intussusception, which can provide guidance for people in future clinical work. Case Presentation: A 51-year-old female was admitted to the hospital with "abdominal pain for 1 month". The enhanced CT of the abdomen suggested a lipoma in the left lower quadrant and a proximal intussusception. After excluding surgical contraindications, laparoscopic exploration was performed on the second day of admission, which showed a small amount of ascites in the abdominal cavity, a small intestine-small intestine type intussusception about 20 cm from the ileocecal area, and about 140 cm from the ileocecal area, a mass about 2*4 cm in size was palpable by laparoscopic intestinal forceps, which was protruded into the intestinal cavity with a soft texture and sound mobility. A 5 cm-length incision was made above the mass to dissect into the abdomen layer by layer, and the diseased intestine was dislodged outside the abdominal cavity with oval forceps. The intestine was reduced by hand and observed for half an hour after reduction, and the blood circulation and peristalsis of the intestine were still sound. The intestine was dissected at 2 cm from the upper and lower margins of the mass, using linear anastomosis to operate small intestine side-to-side anastomosis. The intestine was opened concurrently and closed with a linear anastomosis, using 3-0 absorbable thread to reinforce anastomosis intermittently. The procedure went smoothly and the patient was discharged on the 5th postoperative day. Conclusion: The small intestinal lipoma combined with small intestinal intussusception is rare in clinical practice and needs to be diagnosed by asking history detailedly, physical examination, and relevant ancillary tests such as abdominal CT. Laparoscopic-assisted small incision surgery for adult intussusception combines the advantages of laparoscopic surgery and laparotomy, operating simply and easily.